Maternal risk factors in cleft lip and palate: case control study - N. Natsume, T. Kawai, N. Ogi, W. Yoshida (Blackwell Synergy, 2000)
Both hereditary and environmental factors have been implicated in the development of cleft lip, or palate, or both.1 We have previously reported an epidemiological case control study in which we found that pregnant mother’s dietary preference for green vegetables and dairy products might have some effect on incidence of clefts.2–4 In the present paper, we report further results from the same study.